1986
DOI: 10.1016/s0735-1097(86)80355-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of pulsed energy delivery to minimize tissue injury resulting from carbon dioxide laser irradiation of cardiovascular tissues

Abstract: The carbon dioxide (CO2) laser has been utilized for preliminary intraoperative cardiovascular applications, including coronary endarterectomy and ventricular endocardiectomy. CO2 lasers used for these applications have been operated in the continuous wave, chopped or pulsed mode at low peak powers. To evaluate the extent of boundary tissue injury, continuous, chopped and pulsed energy delivery of CO2 laser emission was used to bore through 192 5 mm thick myocardial slices in air. Continuous, chopped and pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…Therefore, higher levels of collateral damage are expected with low-power, very short pulse ablation modalities, due to the thermal and structural components of tissue ablation. This is in agreement with the conclusions of Deckelbaum et al [14], who showed that, at sufficiently high levels of the average power, the collateral damage caused by infrared radiation will be optimally reduced.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, higher levels of collateral damage are expected with low-power, very short pulse ablation modalities, due to the thermal and structural components of tissue ablation. This is in agreement with the conclusions of Deckelbaum et al [14], who showed that, at sufficiently high levels of the average power, the collateral damage caused by infrared radiation will be optimally reduced.…”
Section: Discussionsupporting
confidence: 93%
“…Noguera et al set up a thermocouple device to monitor the temperature at the tissue interface. Other groups have used pulsed delivery of laser energy as opposed to continuous wave laser delivery, and it has been suggested that pulsed delivery minimizes collateral thermal damage [184]. Other groups have used photo-enhancing dyes and laser wavelengths specific to the chromophore's peak absorption to localize heat at applied areas.…”
Section: Laser Welding and Soldering Laser Weldingmentioning
confidence: 99%
“…Unlike the CO 2 laser that is commonly used in surgical DMR, the Ho:YAG laser has profound acoustic effects due to its differences in absorption coefficient and laser pulse parameters (high peak power and short pulse duration). [35][36][37][38][39] The CO 2 laser produces confined photothermal ablative effects with a very thin zone of adjacent thermal injury and precise channel borders, but cannot be transmitted via conventional fiberoptics and cannot be used for catheter-based DMR applications. 36,37 The short pulsed (Ho:YAG or excimer) lasers cause photothermal and predominantly photo-acoustic ('shock-wave') tissue effects.…”
Section: Laser Myocardial Tissue Interactionsmentioning
confidence: 99%
“…[35][36][37][38][39] The CO 2 laser produces confined photothermal ablative effects with a very thin zone of adjacent thermal injury and precise channel borders, but cannot be transmitted via conventional fiberoptics and cannot be used for catheter-based DMR applications. 36,37 The short pulsed (Ho:YAG or excimer) lasers cause photothermal and predominantly photo-acoustic ('shock-wave') tissue effects. These lasers can be transmitted via silicabased fibers, inducing irregular channel borders and large zones of collateral tissue injury.…”
Section: Laser Myocardial Tissue Interactionsmentioning
confidence: 99%